Pengembangan Permainan Tradisional Didi Lauro untuk Menanamkan Nilai Moral Anak Usia Dini di Kota Palu - Rosmiani, Rosmiani; Agustan, Agustan; Asfar, Muhammad Idham; M, Armina (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2025)
This study was conducted to assist teachers in instilling moral values in early childhood through traditional games. By using a research and development approach using the four D model, the research subjects consisted of fifteen teachers at TK Negeri Pembina North Palu to describe the development of Didi Lauro traditional games to instill moral values of early childhood in Palu City, describe the development design of Didi Lauro traditional games to instill moral values of early childhood in Palu City, and describe the level of practicality and effectiveness of Didi Lauro traditional games to instill moral values of early childhood in Palu City. The data analysis technique used is descriptive qualitative and descriptive quantitative by describing the findings qualitatively and quantitatively. An overview of the level of need for the development of traditional Didi lauro games to instill moral values for early childhood in Palu City, in four aspects; (1) curriculum, (2) modules, (3) props, and (4) instruments. The level of need for the curriculum is 66.6%. module 60%, props 53.3%, and instruments 73.3%. The development design includes the design of game patterns, terms, and songs that are sung according to teacher responses reaching 80%, the validity of the practicality of the game reaches 80% on the indicators (a) easy to understand, (b) fun, (c) entertaining, and (d) right on target. The validity of the effectiveness of the game is 73.3% indicating (a) fast in achieving the target, (b) short in the use of time, and (c) clarity of the results found. These results show that Didi lauro traditional games have high practical validity and effectiveness to instill moral values in early childhood in Palu City.